Ghostlight - Johnston, Bret Anthony 1971- (University of Texas Press, 2022)
"Keith Carter describes this new project as "an exploration of Southern wetlands: swamps, bogs, bayous, baygalls, and marshland-plus some critters." It is that, but for those who know Carter's work it's also instantly identifiable as his own brand of what might be called "Bayou Gothic." Carter is a master at capturing ghostly, ethereal light and his home ground of East Texas has it in abundance. These are fine-art photographs of a particular landscape, one that stretches across the South, and its haunting qualities are well-suited to an eye like Carter's"--